Junie B., first grader : cheater pants - Park, Barbara; Brunkus, Denise (New York : Scholastics, 2004)
When her father will not let her stay up late to do her homework, first grader Junie B. copies a classmate's paper.
"A Stepping Stone Book."
G2
Keywords: Cheating -- Fiction; Schools -- Fiction; Humorous stories